2019
DOI: 10.3390/children6060078
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Massage Therapy Research: A Narrative Review

Abstract: This narrative review on pediatric massage literature from the last decade suggests that massage therapy has positive effects on several pediatric conditions. These include preterm infant growth, psychological problems including aggression, gastrointestinal problems including constipation and diarrhea, painful conditions including burns and sickle cell, muscle tone disorders including cerebral palsy and Down syndrome, and chronic illnesses including diabetes, asthma cancer, and HIV. Potential underlying mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 75 publications
3
41
0
3
Order By: Relevance
“…Although intranasal OT does not appear to influence basal endogenous concentrations (Lee et al, 2018), it is still possible that it might enhance stimulus-evoked ones. Depending on its intensity, massage can also influence either sympathetic or parasympathetic nervous system responses via skin pressure receptors (Field, 2010(Field, , 2019 which raises the additional possibility that OT is influencing neural responses via facilitating vagal responses to pressure receptor activation (A-β fibers) as well as via CT-fibers. Indeed, previous studies have reported that OT can influence both parasympathetic (Kemp et al, 2012) and sympathetic (De Oliveira et al, 2012) nervous system activity.…”
Section: Potential Mechanisms Involved In Intranasal Ot-evoked Facilimentioning
confidence: 99%
See 1 more Smart Citation
“…Although intranasal OT does not appear to influence basal endogenous concentrations (Lee et al, 2018), it is still possible that it might enhance stimulus-evoked ones. Depending on its intensity, massage can also influence either sympathetic or parasympathetic nervous system responses via skin pressure receptors (Field, 2010(Field, , 2019 which raises the additional possibility that OT is influencing neural responses via facilitating vagal responses to pressure receptor activation (A-β fibers) as well as via CT-fibers. Indeed, previous studies have reported that OT can influence both parasympathetic (Kemp et al, 2012) and sympathetic (De Oliveira et al, 2012) nervous system activity.…”
Section: Potential Mechanisms Involved In Intranasal Ot-evoked Facilimentioning
confidence: 99%
“…Massage applied with a moderate pressure is also a pleasant form of affective touch and has great potential in therapeutic applications including reducing pain and stress and enhancing immune function, which may additionally activate non-C-type fibers as it has been shown to be related to the stimulation of pressure receptors under the skin (Field, 2010(Field, , 2019. Animal models have provided evidence that massage-like stroking to rats could produce an analgesic effect, with reduced blood pressure and cortisol levels (Agren et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Infant massage is another physical contact‐based intervention that was designed to facilitate the parent–infant bonding process, including adolescent mothers and infants (Field, ). A review of the literature from 2008–2018 (Field, , ), reveals robust benefits for preterm infants including greater weight gain, shorter hospital stays, greater developmental gains, greater pain tolerance, and reduced parental stress. Fewer studies have been conducted on full‐term newborns and have focused on frequently reported problems parents report to paediatricians, including hyperbilirubinemia, irritability, and sleep disturbances.…”
Section: Early Physical Contactmentioning
confidence: 99%
“…Field () found that adolescent mothers who used infant massage had infants with greater self‐regulation, decreased fussiness, and improved affect during parent‐infant play (Field, ). Field () notes the underlying mechanism of infant massage is increased vagal activity, which leads to decreased stress hormones (cortisol) and increased natural killer cell number and activity. Natural killer cells help combat bacterial, viral, and cancer cells as well as enhance immune function.…”
Section: Early Physical Contactmentioning
confidence: 99%
“…A number of systematic reviews have also been conducted to gather evidence of massage therapy in paediatrics [27,44,45,46]. Field conducted a narrative review on summarising the literature on massage therapy in the past decade and showed that this intervention may have bene cial effects on many paediatric conditions [47]. Although massage is commonly used in infants and children with various conditions, the evidence of the therapeutic effects is not strong enough to support its usual use due to the biases of many previous studies.…”
Section: Massage Therapymentioning
confidence: 99%